Rational use of residential digesters for sewage treatment with Carbon Credits - Godoy Júnior, Ederaldo; Camargo, José Rui; Silva, João Lucio Mariano da; Jesus, Ricardo Osmar de; Silveira, José Luz; Danieletto, José Roberto Bertoncello (Trans Tech Publications, 2013)
The present work aims at decentralization of sewage treatment and eco-efficient way of enabling the deployment of residential digesters to treat only the water with high organic load without overloading the system, avoiding the drag of sludge and effluent untreated into the urban network of collection. For this purpose we developed a low-cost technology that treats sewage in the house of the citizen, thus avoiding that large stations aerobic treatment of sewage and its result regarding the large demands for energy and area: the generation and disposal of biogas smelly collection networks in urban, high production and disposal costs aerobic sludge, the disposal of sewage in fresh water bodies causing eutrophication of waters and spread of diseases hydro transmitted. The system proposed digester residential removes about 80% of the organic load of sewage without the use of any electromechanical element, and also allows to collect the biogas produced subsequently be used for energy or simply be burned to hygiene and / or crediting of carbon. Basically, the system comprises three anaerobic digesters in upflow sludge bed, arranged in series forming cascade phase separator with solid-liquid gas-shaped coil. Used to treat wastewater with high organic load coming from the toilet and the kitchen sink. Then the waters with low organic load coming from the baths, sinks and laundry, are used to dilute and improve the quality end of the anaerobically treated effluent in a sustainable manner. Social and environmental technology developed aligns with the guidelines of the National Water Agency and the Kyoto Protocol, whose goal is to reduce greenhouse gases. © (2013) Trans Tech Publications, Switzerland.
Keywords: Biogas; Carbon Credits; Ecoefficient; Residential digesters; Sewage treatment; Aerobic sludge; Aerobic treatment; Anaerobic digester; Carbon credits; Disposal costs; Electromechanical elements; Fresh Water; High organic; KYOTO protocol; Low organic load; Low-cost technology; Organic load; Phase separators; Solid-liquid; Treated effluent; Urban networks; Water agencies; Carbon; Emission control; Eutrophication; Liquefied gases; Pulp digesters; Sludge disposal; Sustainable development; Wastewater disposal; Wastewater treatment; Effluents